Trends in all-cause mortality and major causes of death between 2007 and 2018 among patients with diabetes in Taiwan - Wang, Jun-Sing; Wu, Yi-Ling; Ou, Horng-Yih; Yang, Yi-Sun; Hsu, Chih-Cheng; Hwu, Chii-Min (Frontiers in Endocrinology, 2022)
Optimal control of diabetes and relevant risk factors substantially reduce the risks of chronic complications and mortality. We investigated all-cause mortality rate and major causes of death between 2007 and 2018 in patients with diabetes in Taiwan. This study was conducted using data from Taiwan National Health Insurance Research Database. We selected patients with diabetes diagnosed between 2007 and 2017 (grouped according to the year of diabetes diagnosis 2007-2010 vs. 2011-2017). Information on mortality and causes of death by the end of 2018 was confirmed through linking to the National Death Registry. Standardized mortality rate (SMR) were calculated by weighting the World Health Organization (WHO) standard population (WHO 2000-2025). More than 2.7 million of patients with diabetes were analyzed and a total of 566121 deaths were identified. Overall, the SMR was 11.72 per 1000 person-years. Patients with diabetes diagnosed in 2011-2017 had a lower SMR (8.42 vs. 12.92 per 1000 person-years) than those diagnosed in 2007-2010. Similar finding were noted regarding the major causes of death (cancer, diabetes, heart disease, hypertensive disease, and cerebrovascular disease). Compared with patients who were diagnosed in 2008-2010, those who were diagnosed in 2011-2014 and 2015-2018 had a higher 3-year survival rate (0.9356 vs. 0.9438 vs. 0.946, log-rank test p<0.001) after the diagnosis of diabetes. Patients who were diagnosed with diabetes after 2011 had a lower rate of all-cause mortality and major causes of death, compared with those who were diagnosed before 2010 in Taiwan.